Peningkatan Kesuburan Tanah Gambut Melalui Pemberian Dolomit dan Penanaman Tanaman Penutup Tanah Mucuna bracteata - Nanda Intan Habibah; Wawan Wawan; Gunawan Tabrani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
Theresearch aims to improve the peat soilfertility (chemical and physical soil properties) through the giving of dolomite and planting of legume cover cropMucuna bracteata. Theresearch was conducted at Kualu Nanas Village, Tambang, Kampar, Riau from September 2017 to February 2018. The researchused Split Plots Design with a basic pattern of Completely Randomized Design. The main plot is Mucuna bracteatawhich consists of 2 levels, without and using a cover crop of Mucuna bracteata. The subplot is the dosesof dolomite fertilizer consisting of 4 levels, namely, 0.0ton.ha-1, 0.5ton.ha-1, 1.0ton.ha-1, 1.5ton.ha-1 The observedparameters were soil water content, water holding capacity, pH soil, soil organic carbon, N-total soil,P-total soil, K-total soil, cation exchange capacity (CEC), exchangeable base, base saturation, LCC M. bracteata biomass, the total of LCCM. bracteata root nodules, the total of LCC M. bracteataeffective root nodules and the tendrils lengthof LCC M. bracteata. The results showed that the planting of LCC M. bracteata increasing the saturation of peat soil bases by 299.12% if the dolomite doses was increased from 0.5 ton.ha-1 to 1.0 ton.ha-1 and 1.5 ton.ha-1. The planting of LCC M. bracteata and thegiving of dolomite can increase the fertility of peat soils such as pH, N-total, exchangeable bases, CEC and base saturation. Keywords : soil fertility, peat, dolomite, Mucuna bracteata.